Provision of Corporate Guarantee Between a Bank and Commanditaire Vennootschap as Debt Insurer - Ghansham Anand; Angelina Uirianto; Gabriele Edria Tjoputra (International Journal of Science and Society, 2023)
This study was to find out the provision of corporate guarantee between the bank and limited partnership as the guarantor based on the corporate guarantee deed. This study used a normative juridical method emphasizing the science of the law by examining the prevailing legal norms in society. Using this method, it was concluded that the legal consequence of the corporate guarantee deed between the bank and limited partnership as a corporate guarantor is an agreement that binds the partners of limited partnership. In addition, legal protection for the bank is by changing the position of limited partnership's partners as a personal guarantee.